The Effect of Health Education by Using Leaflet Media to Increase the Knowledge of Hypertension Patients in Outpatients At South Tapanuli District Hospital: The Effect of Health Education by Using Leaflet Media to Increase the Knowledge of Hypertension Patients in Outpatients At South Tapanuli District Hospital - Ramadhini, Delfi; Ritonga, Nefonavratilova; Siregar, Yenni Farida; Aswan, Yulinda (Jurnal Kesehatan Ilmiah Aufa Royhan, 2021)
Hypertension or high blood pressure is a chronic condition characterized by increased pressure on the walls of arteries. The results of the Basic Health Research (Riskesdas) 2018 showed that the prevalence of hypertension increased compared to Riskesdas 2013, which rose from 25.8% to 34.1%. The purpose of this study was to determine the effect of health education by using leaflet media to increase the knowledge of hypertension patients in outpatients at South Tapanuli District Hospital. The research method used was Quasy Experiment with One group pre-post test design in one group design. The sample in this study amounted to 31 people. The data obtained were processed using the Wilcoxon Sign Rank Test. The results showed that there was an influence of health education on increasing knowledge of patients with hypertension in outpatients in South Tapanuli District Hospital,where before being given health education, respondents had 7 knowledge worth 9 people(29,0%), and after being given health education respondents had 10 knowledge totaling 10 people (32,3%). Based on the Wilcoxon statistical test results obtained p-value = 0,000 <0.005. Suggestions of this research can be used as a new source in increasing the knowledge of hypertension sufferers, and further researchers can use the slide show method or lecture method.